ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN PADA UNIT KERJA MAHKAMAH AGUNG DI WILAYAH RIAU DAN KEPRI DENGAN KOMITMEN ORGANISASI SEBAGAI FAKTOR MODERASI - M. Irwan Tofani; Amir Hasan; Nasrizal Nasrizal (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
This study aims to prove The Influence of The Workload, Utilization of information Technology, Planning, Administration, Human Resources, and Procurement of Goods and Services Towords Budgeting Absorption with Organizational Commitment as a Moderating Factor. This type of research was carried out in The District Court and The Religious Court in The Jurisdiction of Riau Supreme Court and The Riau Riligioues Supreme Court. This research was a survey research by census method, while the distribution technique used a questionnaire distributed to The Mandate of Budget Users, Resolve Making Officer, Tresures of Expenditure and Goods, Service Procurement Officer at the District Courts and The Religious Courts in The Jurisdiction Of Riau Supreme Court and The Riau Religius Supreme Court and Riau Island, Total questionnaires distributed were 165 as many as 138 were returned questionnaires. Data analysis was performed by examining the Stuctural Equation Model (SEM) method based on Partial Least Squares (PLS). From the test values of each independent variable on the dependent variable the end result was Utilization of Information Technologi, Planning, Administration, Human Resources, and Procurement of Goods and Service Towords Budgeting Absorption, While The Workload does not affect Budgeting Absorption. The Commitment of Management Also has a significant effect on Budgeting Absorption, The Commitment of Management was able to influence the relationship of Human Resouces to Budgeting Absorption, but could not strengthen the relationship between the outlining and budgeting absorption.The results also showed that R2 was 0,642 which explained that the percentage contribution of the influence of the independent variable ( The Utilization of Information Technology, The Outlining, The Management, The Human Resources, and The Procurement of Goods and Service ) to the dependent variable ( Budgeting Absorption) was 64,2 % while the rest 35,8 % was influenced by other variables that were not included in this study. Penelitian ini bertujuan untuk membuktikan pengaruh Beban Kerja, Pemanfaatan Tekhnologi Informasi, Perencanaan, Administrasi, Sumber Daya Manusia, Dan Pengadaan Barang Dan Jasa Terhadap Penyerapan Anggaran dengan Komitmen Organisasi Sebagai Faktor Moderasi. Penelitian ini dilakukan pada Pengadilan Negeri dan Pengadilan Agama di Wilayah Hukum Pengadilan Tinggi Riau dan Pengadilan Tinggi Agama Riau. Penelitian ini merupakan penelitian survey dengan metode sensus, sedangkan teknik penyebarannya menggunakan kuesioner yang disebarkan kepada kepada Kuasa Pengguna Anggaran (KPA), Pejabat Pembuat Komitmen (PPK), Pejabat Penandatangan Surat Perintah Membayar (PPSPM), Bendahara Pengeluaran dan Pejabat Penggadaan Barang/Jasa pada Pengadilan Negeri dan Pengadilan Agama di Wilayah Hukum Pengadilan Tinggi dan Pengadilan Tinggi Agama Riau dan Kepri, kuesioner yang disebarkan 165, sebanyak 138 kuesioner yang kembali. Analisis data dilakukan dengan pengujian metode Struktural Equation Model (SEM) berbasis Partial Least Squares (PLS. Dari nilai uji masing-masing variabel independen terhadap variabel dependen memperoleh hasil bahwa Pemanfaatan Tekhnologi Informasi, Perencanaan, Administrasi, Sumber Daya Manusia, Dan Pengadaan Barang Dan Jasa berpengaruh terhadap Penyerapan Anggaran, sedangkan Beban Kerja tidak berpengaruh terhadap Penyerapan Anggaran. Komitmen Organisasi juga pengaruh signifikan terhadap penyerapan anggaran, Komitmen Organisasi mampu mempengaruhi hubungan sumber daya manusia terhadap penyerapan anggaran, namun tidak bisa memperkuat hubungan antara perencanaan terhadap penyerapan anggaran. Hasil penelitian juga menunjukkan hasil dimana R2 sebesar 0.642 dimana ini menjelaskan bahwa persentase sumbangkan pengaruh variabel independen (Beban Kerja, Pemanfaatan Tekhnologi Informasi, Perencanaan, Administrasi, Sumber Daya Manusia, Dan Pengadaan Barang Dan Jasa terhadap variabel dependen (Penyerapan Anggaran.